(untitled) (Economic and Political Thought, 2012)
The article aims to highlight the humanization of the contemporary economy and, what is connected with that, the necessity to take under broader consideration the factor of culture in the analysis of economic phenomena. The discussion has a theoretical character and results from research being carried out for several years by Warsaw School of Economics in cooperation with the scholars of Lazarski University in Warsaw. The research concerned cultural conditions of location and interdisciplinary formation of principles of balanced economic development. The basis for the theses formulated in the article is a methodological consideration of a broadened concept of “institutional economics”, which makes it possible to take into consideration the so-called “soft” factors and development conditions in the interpretational analysis. As culture is a manner of speaking about collective identities, it is becoming an inseparable element of exercising choice between economic culture and barbarism. The collective conscience of the entities of social and economic life should move faster towards contemporary institutions’ operating in the modern civilization style. Adoption of Prof. A. Kłosowska’s statement that culture is also the behavior of people involved in economic processes together with the products and results of such behavior can help economists in the promotion of these processes. The general conclusion is that it is necessary to analyze economic phenomena in a broader, humanistic and scientifically interdisciplinary manner.